A complete Fourier‐synthesis‐based backbone‐conformation‐dependent library for proteins. Issue 2 (8th February 2021) - Tronrud, Dale E.; Karplus, P. Andrew
Abstract : A conformation‐dependent library of target values for protein main‐chain bond angles was determined using a variable‐resolution two‐dimensional Fourier analysis. Abstract : While broadening the applicability of (ϕ/ψ)‐dependent target values for the bond angles in the peptide backbone, sequence/conformation categories with too few residues to analyze via previous methods were encountered. Here, a method of describing a conformation‐dependent library (CDL) using two‐dimensional Fourier coefficients is reported where the number of coefficients for individual categories is determined via complete cross‐validation. Sample sizes are increased further by selective blending of categories with similar patterns of conformational dependence. An additional advantage of the Fourier‐synthesis‐based CDL is that it uses continuous functions and has no artifactual steps near the edges of populated regions of ϕ/ψ space. A set of libraries for the seven main‐chain bond angles, along with the ω and ζ angles, was created based on a set of Fourier analyses of 48 368 residues selected from high‐resolution models in the wwPDB. This new library encompasses both trans ‐ and cis ‐peptide bonds and outperforms currently used discrete CDLs.